VD_FINDINFO HC / 2012 / 127 vom 9. Februar 2012 - VD Tribunal cantonal (2012)
INTERDICTION DE L'ARBITRAIRE, SUSPENSION DE LA PROCÉDURE, LÉGITIMATION ACTIVE ET PASSIVE | 126 CPC (CH), 319 let. b ch. 1 CPC (CH), 320 CPC (CH), 321 CPC (CH), 405 al. 1 CPC (CH)